2017
DOI: 10.1002/cncr.31108
|View full text |Cite
|
Sign up to set email alerts
|

The impact of physical activity on fatigue and quality of life during and after adjuvant treatment for breast cancer

Abstract: PA, especially its frequency, is an important determinant of fatigue and QoL during adjuvant treatment for BC. The promotion of regular PA among women who are receiving treatment for BC may be an effective way to reduce fatigue and improve QoL. Cancer 2018;124:797-806. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…Improvements in medical and behavioural treatments with breast cancer have led to a substantial number of individuals achieving a normal life expectancy . Physical activity (PA) is one such intervention that can reduce breast cancer incidence and improve quality of life (QoL) . PA interventions such as strength and resistance training, aerobic exercise, and brisk walking following breast cancer diagnosis have been shown to be associated with improved survival rates and psychosocial health outcomes, increase levels of PA, and reduce fatigue .…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in medical and behavioural treatments with breast cancer have led to a substantial number of individuals achieving a normal life expectancy . Physical activity (PA) is one such intervention that can reduce breast cancer incidence and improve quality of life (QoL) . PA interventions such as strength and resistance training, aerobic exercise, and brisk walking following breast cancer diagnosis have been shown to be associated with improved survival rates and psychosocial health outcomes, increase levels of PA, and reduce fatigue .…”
Section: Introductionmentioning
confidence: 99%
“…150 min of at least moderate PA per week). In a previous cohort study [36], 15% of breast cancer patients ( n = 466) managed to comply with these recommendations. Considering the fact that patients with factors facilitating PA practice are twice as likely to comply with these recommendations (Odds Ratio = 2), with an alpha risk of 5% and a power of 80%, 660 cancer patients will be included (220 per cancer localization).…”
Section: Methodsmentioning
confidence: 99%
“…Literature have shown benefits of regular physical activity (PA) during and after BC treatment, particularly in terms of improving the quality of life (QoL) (Manneville et al, 2018 ). Several randomized controlled trials have shown that appropriate physical activity (PA) during and after cancer treatment improved patients' QoL (Mishra et al, 2012a , b ).…”
Section: Introductionmentioning
confidence: 99%